Interaction of Blastomyces dermatitidis, Sporothrix schenckii, and Histoplasma capsulatum with Acanthamoeba castellanii - Steenbergen, Judith N. (American Society for Microbiology, 2004)
Several dimorphic fungi are important human pathogens, but the origin and maintenance of virulence in these organisms is enigmatic, since an interaction with a mammalian host is not a requisite for fungal survival. Recently, Cryptococcus neoformans was shown to interact with macrophages, slime molds, and amoebae in a similar manner, suggesting that fungal pathogenic strategies may arise from environmental interactions with phagocytic microorganisms. In this study, we examined the interactions of three dimorphic fungi with the soil amoeba Acanthameobae castellanii. Yeast forms of Blastomyces dermatitidis, Sporothrix schenckii, and Histoplasma capsulatum were each ingested by amoebae and macrophages, and phagocytosis of yeast cells resulted in amoeba death and fungal growth. H. capsulatum conidia were also cytotoxic to amoebae. For each fungal species, exposure of yeast cells to amoebae resulted in an increase in hyphal cells. Exposure of an avirulent laboratory strain of H. capsulatum to A. castellanii selected for, or induced, a phenotype of H. capsulatum that caused a persistent murine lung infection. These results are consistent with the view that soil amoebae may contribute to the selection and maintenance of certain traits in pathogenic dimorphic fungi that confer on these microbes the capacity for virulence in mammals.